Strengthening Research and Practice in Community Health Systems: A Research Agenda and Manifesto - Moses Tetui; Anna-Karin Hurtig; Frida Jonsson; Eleanor Whyle; Joseph Zulu; Helen Schneider; Alison Hernandez; The Chaminuka Collective (Kerman University of Medical Sciences, 2022)
While there have been increased calls for strengthening community health systems (CHSs), key priorities for this field have not been fully articulated. This paper seeks to fill this gap, presenting a collaboratively defined research agenda, accompanied by a 'manifesto' on strengthening research and practice in the CHS. The CHS research agenda domains were developed through a modified concept mapping process with a team of 33 experts on the CHS including policy-makers, implementers and researchers from institutions in six countries: Uganda, Guatemala, South Africa, Sweden, Tanzania and Zambia. The process began remotely with brainstorming research priorities and concluded in a one-week workshop that was held in Zambia where priorities for strengthening CHS were discussed, grouped into domains, interpreted, and drafted into a collective declaration. Eight domains of research priorities for CHSs were identified: clarifying the purpose and values of the CHS, ensure inclusivity; design, implementation and monitoring of strategies to strengthen the CHS; social, political and historical contexts of CHS; community health workers (CHWs); social accountability; the interface between the CHS and the broader health system; governance and stewardship; and finally, the ethical methodologies for researching the CHS. By harnessing a set of diverse and rich experiences and perspectives on CHS through a structured process, a multifaceted research agenda and manifesto that transcend context, disciplines and time were developed. We posit this as an entry into greater debate and diversity in the field as we continue to find ways to strengthen research and practice in the CHS.